State ownership, the institutional environment, and auditor choice: Evidence from China - Wang, Qian; Wong, T.J.; Xia, Lijun (Journal of Accounting and Economics, 2008)
This paper finds that compared with non-state-owned firms, Chinese state-owned enterprises controlled by province, city, and county governments (local SOEs) are more likely to hire small auditors within the same region (small local auditors). In regions with less developed institutions, SOEs controlled by central government (central SOEs) also have such a tendency. However, the tendency of local and central SOEs to hire small local auditors is attenuated as the institutions develop. This auditor choice pattern is likely to be explained by SOEs’ lack of demand for large or non-local auditors, small local auditors’ superior local knowledge, and SOEs’ collusion incentives.